(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article examines the priority directions for the establishment of free economic zones in Uzbekistan. Also, the formation of legal norms for foreign direct investments in accordance with international standards, attracting more investments to the country’s economy, structural changes in the economy. Proposals and recommendations on the establishment of SEZs and increasing investment activity in them were formulated.